Incidence of Non Habit Associated Oral Squamous Cell Carcinoma among Patients in a Private College Hospital - A Retrospective Study - M. Sagana1 , Pratibha Ramani2 , M. Jeevitha3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Oral squamous cell carcinoma is considered as one of the major prevalent oral cancers in the world. Themajor risk factors considered are tobacco and alcohol. However, in the present there is an increasedincidence of non habit associated squamous cell carcinoma. This study aims to evaluate the incidence of nonhabit associated squamous cell carcinoma visiting our college hospital. A total of 50(n=50) patients withsquamous cell carcinoma visited Saveetha Dental College were included in this study. Datas were collectedby reviewing the patients records and analysed the data of 86000 patients visited between June 2019 andMarch 2020. All the datas were recorded and analysed statistically using SPSS software. From the analysisthrough SPSS, it was found that the overall incidence of non habit associated squamous cell carcinomawas 56% with male predilection and it was found to be statistically significant(p<0.05). The results of ourstudy shows that there is a significant number of patients without habits presented with oral squamous cellcarcinoma with a cause unknown in our hospital.